Project BORN FREE. Evaluation of Educational Change Process in Project BORN FREE Institutions 1976-1977. Technical Report No. 6 - Keierleber, Dennis L.; Hansen, L. Sunny; Minnesota Univ., Minneapolis. Coll. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
BORN FREE is a collaborative effort of university-based counseling psychologists and field-site educators to reduce career-related sex stereotyping in 14 educational institutions and to broaden the range of career options of women and men. The project focuses on the development of training modules (materials, workshops, and videotapes) for administrators, teachers, counselors, and parents at all educational levels. The Rand Model, emphasizing initiation, implementation, and outcomes and continuation as three phases in educational change processes, provides the basis for this report. The conceptual framework for evaluating educational change is delineated, including definitions, assumptions, relevant characteristics of project and institutions, and characteristics of the three stages. Evaluation methodology is described, including data collection, analysis, and limitations. An analysis of change process in BORN FREE institutions includes influential factors and adaptations during the first-year implementation. Outcomes and continuation are discussed in relation to attitude and behavior change and institutional and project factors affecting continuation plans for the second year. A summary is presented with a discussion of the tentative nature of conclusions based on first-year experiences. Appendices include the adapted conceptual framework for educational change and outlines of data collection instruments. (Author/NRB)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Women's Educational Equity Act Program.
Contract Number: 565AH70023.
ERIC Note: For related documents see CG 014 752-757 and ED 150 493-495.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Keywords: Careers; Educational Change; Elementary Secondary Education; Equal Opportunities (Jobs); Institutional Evaluation; Material Development; Postsecondary Education; Program Descriptions; Program Evaluation; Program Implementation; Sex Stereotypes; Project BORN FREE; Reports, Evaluative